Surface strengthening treatment process of semiconductor wafer

Through ozone water ultrasonic cleaning, laser treatment and plasma deposition processes, the problems of mechanical strength, thermal stability and corrosion resistance of wafer surface are solved, efficient wafer surface strengthening is achieved, and device reliability and yield are improved.

CN120545175AActive Publication Date: 2025-08-26SHANGHAI WELNEW MICRO ELECTRONICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510700991.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-08-26
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

Traditional wafer surface treatment processes have defects in insufficient mechanical strength, chemical damage, insufficient thermal stability and corrosion resistance, which affect device reliability and process yield.

Method used

The multi-step process of ozone water ultrasonic cleaning combined with high-purity nitrogen purge, laser treatment, radio frequency plasma deposition and methane plasma treatment is adopted, including ozone decomposition of organic pollutants, laser nano-scale lattice reconstruction, plasma deposition of high-density silicon nitride layer and methylsilane cross-linking structure formation.

Benefits of technology

Significantly improve the hardness and cleanliness of wafer surface, reduce surface roughness, enhance scratch resistance, and ensure the electrical stability and yield of the device.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a surface strengthening treatment process of a semiconductor wafer, and belongs to the technical field of wafer treatment. According to the method, firstly, ozone water is adopted to cooperate with ultrasonic cleaning, organic pollutants are decomposed through the strong oxidizing property of ozone, inorganic particles are removed in combination with the ultrasonic cavitation effect, dual purification is achieved, an inert atmosphere is constructed through nitrogen purging, and an atomic-scale clean substrate is provided for the follow-up process; secondly, through vacuum laser shallow layer repairing, excimer laser is used for inducing lattice rearrangement, microcracks are eliminated, the surface roughness and hardness are improved, and meanwhile thermal stress deformation is avoided; then, a radio frequency plasma chemical vapor deposition technology is adopted to form a high-compactness amorphous silicon nitride barrier layer, and alkali metal ion permeation is effectively blocked; and finally, methyl silane is introduced through methane plasma treatment, a dynamic cross-linked structure is formed, scratch self-repairing is achieved, the surface hardness after repairing is improved, and the scratch resistance of the wafer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wafer processing and relates to a surface strengthening processing process for a semiconductor wafer. Background Art

[0002] As semiconductor devices develop towards miniaturization and high integration, the impact of wafer surface performance on device reliability and process yield is becoming increasingly significant. Traditional surface treatment processes face the following limitations: First, insufficient mechanical strength. Existing technologies such as chemical mechanical polishing or wet etching can easily cause sub-surface damage to the wafer, resulting in problems such as microcracks and lattice distortion, which reduce the wafer's resistance to bending and impact. Second, corrosion resistance defects are easily generated. Although wet cleaning processes can remove surface contaminants, highly corrosive reagents such as hydrofluoric acid may over-etch the wafer surface, resulting in uneven passivation layer thickness. In addition, traditional surface treatment processes have the problem of insufficient thermal stability. Although high-temperature annealing can repair wafer surface defects, it can cause wafer warping and diffusion shift of the doped region. For ultra-thin wafers, the thermal stress problem is particularly prominent. Therefore, there is an urgent need to develop a wafer surface strengthening process that combines low damage, high uniformity, and low cost to adapt to the processing requirements of semiconductor materials. Summary of the Invention

[0003] The purpose of the present invention is to provide a surface strengthening treatment process for semiconductor wafers.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A surface strengthening treatment process for a semiconductor wafer, wherein the specific steps of the surface strengthening treatment process are as follows:

[0006] S1: Using ozone water ultrasonic cleaning to remove organic pollutants on the surface of the semiconductor wafer, and then using high-purity nitrogen to purge the surface of the semiconductor wafer to obtain semiconductor wafer A;

[0007] S2: Place semiconductor wafer A in a vacuum chamber for laser processing with an energy density of 0.5 to 1.2 J / cm 2 , scanning speed 30-50 mm / s, overlap rate 20%, to obtain semiconductor wafer B;

[0008] S3: Performing radio frequency plasma deposition on semiconductor wafer B by introducing a mixed gas at a pressure of 50-70 Pa and a power of 200-220 W to obtain semiconductor wafer C;

[0009] S4: The semiconductor wafer C is then treated with methane plasma, wherein the methane plasma contains methylsilane and the pulse bias voltage is -500 V, to obtain the semiconductor wafer.

[0010] As a preferred technical solution of the present invention, the concentration of the ozone water in S1 is 60-80 ppm.

[0011] As a preferred technical solution of the present invention, the power of the ultrasound in S1 is 80-100W and the frequency is 26-30kHz.

[0012] As a preferred technical solution of the present invention, the nitrogen purge rate in S1 is 3.0 to 4.0 L / min, and the nitrogen purge time is 15 to 30 s.

[0013] As a preferred technical solution of the present invention, the pressure in the vacuum chamber in S2 is ≤10 -3 Pa.

[0014] As a preferred technical solution of the present invention, the laser treatment in S2 adopts 248nm KrF excimer laser.

[0015] As a preferred technical solution of the present invention, the mixed gas in S3 is SiH4 / NH3 / He mixed in a volume ratio of (1.5-1.8):(1-1.2):(5-6).

[0016] As a preferred technical solution of the present invention, the radio frequency plasma deposition rate in S3 is 0.5-0.6 nm / s.

[0017] As a preferred technical solution of the present invention, the methane plasma in S4 contains methylsilane with a volume fraction of 3 to 5%.

[0018] As a preferred technical solution of the present invention, the methane plasma deposition temperature in S4 is 130-150° C., and the processing time is 8-12 minutes.

[0019] First, the surface enhancement treatment process of the present invention uses ozone water in conjunction with an ultrasonic cleaning process. The strong oxidizing property of ozone molecules can selectively decompose organic pollutants such as photoresist residues and grease, avoiding the introduction of metal ion impurities. The cavitation effect generated by ultrasound forms microjets and shock waves in the liquid, which further remove inorganic particulate matter through mechanical stripping, achieving dual purification of chemical dissolution and physical stripping. The limitation of ozone concentration can not only ensure the removal of organic matter in a short time, but also avoid excessive etching of the silicon substrate by excessive active oxygen. Subsequent nitrogen directional purge quickly removes the residual liquid film, prevents the increase in interface state density caused by the formation of water marks, and at the same time constructs an inert atmosphere barrier, effectively inhibiting the adsorption reaction of hydroxyl groups on the wafer surface after cleaning with CO2 / H2O in the air, providing an atomic-level clean substrate for subsequent thin film deposition.

[0020] The laser shallow repair process in a vacuum environment uses an excimer laser to achieve non-thermal surface treatment. Precisely controlling the laser energy density induces a controlled phase transition on the wafer surface through photon-phonon coupling. Upon absorbing the photon energy, the amorphous oxide layer undergoes lattice rearrangement, transforming into a dense nanocrystalline structure while simultaneously eliminating microcracks introduced by plasmon etching. A dynamic focusing system is employed during the laser scanning process, controlling grain size through real-time feedback to avoid warping caused by temperature gradients in traditional thermal annealing processes. Laser treatment reduces wafer surface roughness while simultaneously improving surface hardness.

[0021] Utilizing radio frequency plasma chemical vapor deposition (RFPCVD), a highly dense amorphous silicon nitride barrier layer is formed on the wafer surface through plasma dissociation of a SiH4 / NH3 / He gas mixture in a volume ratio of 3:2:5. During deposition, pulsed bias voltage is used to optimize ion bombardment energy, increasing film density while maintaining an optimal hydrogen content to balance internal stress. This film effectively reduces the sodium ion diffusion coefficient, significantly improving barrier performance compared to traditional thermal oxide layers. It effectively blocks the permeation and migration of alkali metal ions during subsequent high-temperature processing, ensuring device threshold voltage stability.

[0022] Methylsilane is introduced as a precursor during methane plasma treatment, and the active hydrogen generated by its decomposition reacts with the sp 3 The hybridized carbon atoms undergo hydrogenation, forming a dynamic Si-CH crosslinked structure. When the surface is scratched, the silanol groups condense with the unsaturated bonds in the DLC film, reconstructing the chemical bonds in the defective area. This self-healing mechanism significantly improves the scratch repair rate, and the repaired surface hardness does not show a significant decrease compared to the original DLC film, attributed to the enhanced energy dissipation caused by the increased crosslinking density. The dynamic crosslinked network also reduces the friction coefficient, significantly improving scratch resistance during wafer transport.

[0023] Beneficial effects of the present invention:

[0024] The semiconductor surface strengthening process of the present invention first uses ozone-ultrasonic cleaning to utilize double purification of oxidative decomposition and cavitation stripping, combined with nitrogen isolation protection, to ensure that the substrate cleanliness reaches the atomic level, laying the foundation for subsequent processes; excimer laser non-thermal melt treatment realizes nanoscale lattice reconstruction, while eliminating microcracks, reducing surface roughness and improving hardness, and there is no thermal stress warping; plasma deposition of high-density silicon nitride layer significantly improves the sodium ion barrier performance, ensuring the electrical stability of the device; methylsilane enhances the DLC network to form a dynamic cross-linked structure, realizing the scratch self-repair function, and the hardness does not show obvious attenuation after repair, effectively improving the scratch resistance during wafer transmission. The semiconductor surface strengthening process of the present invention can significantly improve the yield and reliability of semiconductor devices. DETAILED DESCRIPTION

[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0026] Example 1

[0027] A surface strengthening treatment process for a semiconductor wafer, wherein the specific steps of the surface strengthening treatment process are as follows:

[0028] S1: Using 70 ppm ozone water ultrasonic cleaning to remove organic pollutants on the surface of the semiconductor wafer, the ultrasonic power is 90 W, and the frequency is 28 kHz. Then, high-purity nitrogen is purged on the surface of the semiconductor wafer at a rate of 3.5 L / min and a nitrogen purge time of 20 s, to obtain semiconductor wafer A;

[0029] S2: Place the semiconductor wafer A in a vacuum chamber for laser processing. The laser processing uses a 248nm KrF excimer laser. The pressure in the vacuum chamber is ≤10 -3 Pa, energy density 0.8 J / cm 2 , scanning speed 40mm / s, overlap rate 20%, and obtain semiconductor wafer B;

[0030] S3: Performing radio frequency plasma deposition on semiconductor wafer B by introducing a mixed gas of SiH4 / NH3 / He in a volume ratio of 1.6:1.1:5.5, with a pressure of 60 Pa, a power of 210 W, and a deposition rate of 0.55 nm / s to obtain semiconductor wafer C;

[0031] S4: The semiconductor wafer C is then treated with methane plasma, wherein the methane plasma contains 4% by volume of methylsilane, the pulse bias voltage is -500 V, the deposition temperature is 140° C., and the treatment time is 10 min, to obtain the semiconductor wafer.

[0032] Example 2

[0033] A surface strengthening treatment process for a semiconductor wafer, wherein the specific steps of the surface strengthening treatment process are as follows:

[0034] S1: Using 60 ppm ozone water ultrasonic cleaning to remove organic pollutants on the surface of the semiconductor wafer, the ultrasonic power is 80 W, the frequency is 26 kHz, and then the surface of the semiconductor wafer is purged with high-purity nitrogen at a rate of 3.0 L / min and a nitrogen purge time of 15 s, to obtain semiconductor wafer A;

[0035] S2: Place the semiconductor wafer A in a vacuum chamber for laser processing. The laser processing uses a 248nm KrF excimer laser. The pressure in the vacuum chamber is ≤10 -3 Pa, energy density 0.5 J / cm 2 , scanning speed 30mm / s, overlap rate 20%, and obtain semiconductor wafer B;

[0036] S3: Performing radio frequency plasma deposition on semiconductor wafer B by introducing a mixed gas comprising SiH4 / NH3 / He in a volume ratio of 1.5:1:5, a pressure of 50 Pa, a power of 200 W, and a deposition rate of 0.5 nm / s to obtain semiconductor wafer C;

[0037] S4: The semiconductor wafer C is then treated with methane plasma, wherein the methane plasma contains 3% by volume of methylsilane, the pulse bias voltage is -500 V, the deposition temperature is 130° C., and the treatment time is 8 minutes, to obtain the semiconductor wafer.

[0038] Example 3

[0039] A surface strengthening treatment process for a semiconductor wafer, wherein the specific steps of the surface strengthening treatment process are as follows:

[0040] S1: Using 80 ppm ozone water ultrasonic cleaning to remove organic pollutants on the surface of the semiconductor wafer, the ultrasonic power is 100 W, the frequency is 30 kHz, and then the surface of the semiconductor wafer is purged with high-purity nitrogen at a rate of 4.0 L / min and a nitrogen purge time of 30 s, to obtain semiconductor wafer A;

[0041] S2: Place the semiconductor wafer A in a vacuum chamber for laser processing. The laser processing uses a 248nm KrF excimer laser. The pressure in the vacuum chamber is ≤10 -3 Pa, energy density 1.2 J / cm 2 , scanning speed 50mm / s, overlap rate 20%, and obtain semiconductor wafer B;

[0042] S3: Performing radio frequency plasma deposition on semiconductor wafer B by introducing a mixed gas of SiH4 / NH3 / He in a volume ratio of 1.8:1.2:6, with a pressure of 70 Pa, a power of 220 W, and a deposition rate of 0.6 nm / s to obtain semiconductor wafer C;

[0043] S4: The semiconductor wafer C is then treated with methane plasma, wherein the methane plasma contains 5% by volume of methylsilane, the pulse bias voltage is -500 V, the deposition temperature is 150° C., and the treatment time is 12 minutes, to obtain the semiconductor wafer.

[0044] Comparative Example 1

[0045] The ozone cleaning step in S1 is omitted, and the remaining steps are the same as those in Example 1.

[0046] Comparative Example 2

[0047] The ozone concentration in S1 was reduced to 40 ppm, and the remaining steps were the same as in Example 1.

[0048] Comparative Example 3

[0049] The laser energy density in S2 is 0.3 J / cm 2 , scanning speed 50 mm / s, and the remaining steps are consistent with Example 1.

[0050] Comparative Example 4

[0051] In S3, no methylsilane was added to the methane plasma, and the remaining steps were the same as those in Example 1.

[0052] Comparative Example 5

[0053] The remaining steps were the same as those in Example 1 except that step S2 was omitted.

[0054] Performance Testing

[0055] The hardness of the semiconductor wafers prepared in the examples and comparative examples was measured by nanoindentation method. The hardness value was calculated by pressing the indenter into the material surface under a very small load. The calculation formula is H = P max / A, where P max is the maximum load, A is the contact area, and H is the hardness value. Semiconductor wafers were cut into 1 cm × 1 cm samples. The nanoindenter was calibrated using fused quartz to ensure an accurate indenter-area function. The loading rate was set to 0.5 mN / s, the dwell time was set to 10 s, and the unloading rate was set to 1 mN / s.

[0056] Hardness (GPa) Example 1 11.7 Example 2 11.4 Example 3 10.9 Comparative Example 1 8.5 Comparative Example 2 9.3 Comparative Example 3 7.8 Comparative Example 4 8.9 Comparative Example 5 10.4

[0057] It can be seen from the data of the examples and comparative examples that the semiconductor wafer obtained by the surface strengthening method of the present invention has good hardness.

[0058] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A surface strengthening treatment process for a semiconductor wafer, characterized in that: The specific steps of the surface strengthening treatment process are as follows: S1: Using ozone water ultrasonic cleaning to remove organic pollutants on the surface of the semiconductor wafer, and then using high-purity nitrogen to purge the surface of the semiconductor wafer to obtain semiconductor wafer A; S2: Place semiconductor wafer A in a vacuum chamber for laser processing with an energy density of 0.5 to 1.2 J / cm 2 , scanning speed 30-50 mm / s, overlap rate 20%, to obtain semiconductor wafer B; S3: Performing radio frequency plasma deposition on semiconductor wafer B by introducing a mixed gas at a pressure of 50-70 Pa and a power of 200-220 W to obtain semiconductor wafer C; S4: The semiconductor wafer C is then treated with methane plasma, wherein the methane plasma contains methylsilane and the pulse bias voltage is -500 V, to obtain the semiconductor wafer.

2. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The concentration of the ozone water in S1 is 60-80 ppm.

3. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The power of the ultrasound in S1 is 80-100W, and the frequency is 26-30kHz.

4. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The nitrogen purge rate in S1 is 3.0-4.0 L / min, and the nitrogen purge time is 15-30 s.

5. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The pressure in the vacuum chamber in S2 is ≤10 -3 Pa.

6. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The laser treatment in S2 uses 248 nm KrF excimer laser.

7. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The mixed gas in S3 is SiH4 / NH3 / He mixed in a volume ratio of (1.5-1.8):(1-1.2):(5-6).

8. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The radio frequency plasma deposition rate in S3 is 0.5-0.6 nm / s.

9. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The methane plasma in the S4 contains methylsilane with a volume fraction of 3 to 5%.

10. The surface strengthening treatment process for a semiconductor wafer according to claim 1, characterized in that: The methane plasma deposition temperature in S4 is 130-150° C., and the processing time is 8-12 minutes.

Citation Information

Patent Citations

  • Semiconductor silicon wafer cleaning treatment apparatus and cleaning method

    CN112673458A

  • Semiconductor processing method

    CN113345794A

  • Preparation method of silicon-doped nano-diamond crystal grains

    CN115652420A

  • Hard amorphous carbon film and production thereof

    JP1995054150A

  • Semiconductor substrate and method for manufacturing the same, and method for manufacturing semiconductor device

    US20090115029A1